Integration of forage and food crops grown sequentially on Vertisols under rainfed conditions in the mid-altitude Ethiopian highlands - Tedla, A.; Sherington, J.; Mohamed-Saleem, M.A. (Cambridge University Press, 1994)
Poor drainage of Vertisols in the Ethiopian mid-altitude highlands limits farming operations and cropping in the early rainy season. Thus, traditional crops are grown late in the season on the residual moisture in the dry season when waterlogging is less of a problem. Consequently performance of traditional crops on Vertisols remains below their potentials. The recent introduction of a broadbed and farrow system for improved drainage on Vertisols allows full use of the growing period. This provides the greatest scope for a wide variety of cropping systems in order to increase productivity from these soils. One ccropping option, assessed over a two year period and using improved drainage, was a sequential cropping system. The results of the sequential system demonstrated that two crops can be grown sequentially in a year when Vertisols are drained. These were oats and oats/vetch mixture forages in the early rainy season as the first crop and grasspea and chickpea food crops in the late season as the second croFurther on farm research is needed to study sequential cropping of forages and food crops, under the socio-economic and technical conditions of the farming system in the mid-altitude highlands of Ethiopia.